Umumta‘lim maktablarida basketbol sport seksiyasiga tanlashda xalq harakatli o‗yinlardan foydalanish samaradorligi (SCIENCE and SOCIETY, 2023)
In the article, students of general education schools, their extracurricular activities were selected as the object of re- search. The process of circle training was analyzed on the example of basketball.